Peran Kepala Sekolah Dalam Pengelolaan Kurikulum Merdeka - Imelda; Sumarsih; Connie (UNIVERSITAS BENGKULU, 2025)
This research aims to describe the role of school principals in the management of the Independent curriculum at SD Negeri 64 Lubuklinggau. The research uses a descriptive qualitative method. The research subjects were principals and teachers at SD Negeri 64 Lubuklinggau. Data collection by interview, observation and documentation techniques. The data analysis technique begins with data collection and drawing conclusions. The results of the study show that the role of school principals in the management of the independent curriculum runs in accordance with the stages, namely curriculum planning, curriculum implementation, curriculum evaluation, and follow-up of the independent curriculum at SD Negeri 64 Lubuklinggau, and has a significant impact on improving the quality of learning, especially in terms of improving student competence, both in the academic and character fields. The successful management of the independent curriculum also shows an increase in student involvement in the learning process, an increase in critical thinking skills, and the strengthening of the values of the Pancasila Student Profile in the school environment. However, there is still a need for improvement and improvement in certain parts to be able to maximize the management of the independent curriculum at SD Negeri 64 Lubuklinggau.